Optimalisasi Pencatatan E-commerce pada Perusahaan: Input Data Google Sheets - Syarifah Nadia; Chairil Anwar (Jurnal Kabar Masyarakat, 2024)
This service aims to optimize e-commerce sales recording on the Shopee platform using Google Sheets. The problem faced by companies is the difficulty in managing transaction recording manually which is often time consuming and prone to errors. Service is carried out through field work practice at PT Aliyan Jaya Perkasa. The service results show that integrating Shopee sales data into Google Sheets can increase efficiency and accuracy in managing sales data in real-time. The contribution of this service lies in developing a more structured digital recording process for small and medium businesses.